2018
DOI: 10.30813/ncci.v0i0.1272
|View full text |Cite
|
Sign up to set email alerts
|

Faktor–faktor Yang Mempengaruhi Pengambilan Keputusan Investasi Di Pasar Modal Indonesia

Abstract: <h5><em>The purpose of this research</em><em> to determine what factors affect the return on investment in the Indonesian capital market. By replicating the research conducted by Quershi et al (2012) found 4 (four) factors that influence investment decision making, namely heuristics, risk aversion, financial tools and firm levels of corporate governance. Data analysis technique is quantitative descriptive analysis using primary data with information that is in accordance with respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Hasil koefisien determinasi dapat disimpulkan bahwa kelima variabel independen mempengaruhi variabel dependen sebesar 19%, sedangkan 81% dapat dijelaskan oleh faktor-faktor lain yang tidak dimasukkan ke dalam penelitian. Susilawaty, Purwanto, & Febrina (2018) meneliti mengenai "Faktor-Faktor Yang Mempengaruhi Pengambilan Keputusan Investasi Di Pasar Modal Indonesia". Hasil penelitian menujukkan bahwa heuristic, risk aversion, financial tools dan firm level corporate governance bersama-sama berpengaruh signifikan terhadap investment decision making.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Hasil koefisien determinasi dapat disimpulkan bahwa kelima variabel independen mempengaruhi variabel dependen sebesar 19%, sedangkan 81% dapat dijelaskan oleh faktor-faktor lain yang tidak dimasukkan ke dalam penelitian. Susilawaty, Purwanto, & Febrina (2018) meneliti mengenai "Faktor-Faktor Yang Mempengaruhi Pengambilan Keputusan Investasi Di Pasar Modal Indonesia". Hasil penelitian menujukkan bahwa heuristic, risk aversion, financial tools dan firm level corporate governance bersama-sama berpengaruh signifikan terhadap investment decision making.…”
Section: Pendahuluanunclassified
“…Investor lebih tertarik menanamkan modalnya pada perusahaan yang rendah nilai DER-nya karena risiko atas kegagalan melunasi seluruh kewajiban perusahaan lebih kecil, sehingga harga saham perusahaan dengan nilai DER yang rendah lebih tinggi dibandingkan harga saham perusahaan dengan nilai DER yang besar. Hasil penelitian ini didukung oleh penelitian terdahulu yang dilakukan oleh ( (Rahayu & Utami, 2021); (Susilawaty et al, 2018); (Hutajulu, 2020)) yang menyatakan leverage berpengaruh pada keputusan investasi Harga Saham Berpengaruh Terhadap Keputusan Investasi Harga saham adalah harga saham yang terjadi di pasar bursa efek pada saat tertentu yang ditentukan oleh pelaku pasar, ditentukan oleh permintaan dan penawaran saham yang bersangkutan dipasar 2428 modal (Pratama et al, 2020). Setiap investor pasti menginginkan pembelian dengan harga yang murah dan menjual dengan harga yang tinggi.…”
Section: Pembahasan Profitabilitas Berpengaruh Terhadap Keputusan Inv...unclassified
“…Environmental factors are important factors in determining investment awareness that come from external sources that influence an individual in making an investment. The influence of investors' environmental factors needs to be considered, because they affect investment awareness, investors often involve more than one individual (Susilawaty et al, 2018). Environmental factors are often measured by the country's political, social and economic conditions and the influence of the surrounding environment such as recommendations from friends, co-workers and family (Perdana, 2019).…”
Section: )mentioning
confidence: 99%
“…An investor will avoid risk in a profitable situation by selling shares and will refrain from selling shares in a loss condition (risk avoidance analysis on investment decisions in the Indonesian capital market). Research conducted by Susilawaty et al (2018) conducted in Indonesia in 2018 shows that risk-aversion has a negative effect on an investor's investment decisions. This research is not in line with the research conducted by Qureshi et al (2012) in this research it was found that risk-aversion has a positive influence on an investor's investment decisions.…”
Section: Risk-aversionmentioning
confidence: 99%